Calculation for Acoustic Radiation Force from Rectangular Weakly Focusing Transducer Using the Ray Acoustic Model - YU, Lili; QIAO, Shuchang; SHOU, Wende; LI, Junhua (Archives of Acoustics, 2022)
Based on the ray acoustic model, a new relationship between the radiation force and the acoustic power is studied for a rectangular weakly focusing transducer. The effect of pressure reflection coefficient on this model is discussed. For a totally absorbing target, an approximate closed-form expression is also derived and the performance of this model is compared with that of the far-field integration model. The numerical results show that the agreement is excellent with these two models, which can be both used for correction of measured results, but the formula based on the ray acoustic model can be applied more widely in practice because of its simpler expression. The experimental results show further the effectiveness of the relationship between radiation force and acoustic power for rectangular weakly focusing transducer based on the ray acoustic model. The results presented in this paper are important for application of ultrasound transducers in therapy.